UNIVERSAL BASIC PODCAST: Peak Podcast in the Time of Covideocracy and Zoom Isolationism - Tiplady, Jonty (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Jonty Tiplady Title (English): UNIVERSAL BASIC PODCAST: Peak Podcast in the Time of Covideocracy and Zoom Isolationism Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 98-100 Page Count: 3 Citation (English): Jonty Tiplady, “UNIVERSAL BASIC PODCAST: Peak Podcast in the Time of Covideocracy and Zoom Isolationism,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 98-100.